Foreign Direct Investment in developing countries : Risks and guaranties - LALMI, FATIMA; BOUANAINI, SAMIHA; ADEL, FATIMA ZAHRA (International Journal of Social Sciences and Humanities Research, 2015)
FDI plays an active role in the financing of development in one hand, and technology transfer and strengthening the technical experience of countries , facilitate their integration into the world economy in another hand .While the attraction of these investments and the profitage of its benefits depends on the degree of political, legal, economic and social stability of the host country , the flows are related to the availability of a favorable investment climate to their activity and the existence of insurance coverage against various risks that may be encountered in developing countries. The aim of this study is to identify the various guarantees provided by the developing countries to protect foreign direct investment from non-commercial risks in order to determine the most effective, as well as the presentation of the experiences of some developing countries that have succeeded in attracting this type of investment in order to take advantage of them.
Keywords: insurance, foreign direct investment, developing countries, non-commercial risk